Quality of life reported by patients with ecchymosis following total knee arthroplasty - Gong, Zhibing; Qiu, Hanglin; Zhang, Huantang; Xu, Yanyan; Wu, Rongkai; Zhang, Qianjin; Lin, Hanghui; Wu, Zhaoke; Xu, Fudong; Zhuang, Zhikun; Huang, Changyu (Frontiers in Surgery, 2025)
ObjectivesTo explore the early quality of life (QOL), function, and pain of patients with ecchymosis after total knee arthroplasty (TKA) using Patient-Reported Outcome Measures (PROMs), and to investigate the incidence of post-TKA ecchymosis and its potential risk factors under anticoagulant therapy.MethodsThis single-center observational study included patients who underwent TKA at our center from June 2022 to June 2023. Data on demographic information, surgical details, pre-operative and post-operative laboratory results, imaging data, etc., were collected. Patients were divided into two groups based on the presence or absence of ecchymosis after TKA: the ecchymosis group and the non-ecchymosis group. Patients' QOL postoperatively was assessed using Visual Analog Scale (VAS), Hospital for Special Surgery (HSS) score, and Rand 36-Item Short Form Health Survey (SF-36). A binary logistic regression model was employed to analyze the risk factors for post-TKA ecchymosis.ResultsA total of 138 participants were included, 15 males and 123 females, with a mean age of 67.91 ± 7.24 years and BMI of 25.57 ± 3.85 kg/m2. There were 60 cases in the ecchymosis group and 78 cases in the non-ecchymosis group, resulting in an incidence of post-TKA ecchymosis of 43.48%. The ecchymosis group demonstrated more significant pain and poorer joint function postoperatively, with significantly lower scores in the SF-36 dimensions and 7 subdomains compared to the non-ecchymosis group. Regression analysis suggested that age may be a risk factor for post-TKA ecchymosis.ConclusionsThe incidence of ecchymosis after TKA is high under anticoagulant therapy, leading to increased pain sensitivity, decreased function, and quality of life in patients. Age may be a risk factor for early post-TKA ecchymosis. Incorporating information on ecchymosis into preoperative education and providing appropriate psychological interventions for patients experiencing ecchymosis may be necessary.